Paralomis spinosissima Birstein & Vinogradov 1972 - Olguín, Nicole; Ocampo, Emiliano H.; Farias, Nahuel (Zenodo, 2015)
Paralomis spinosissima Birstein & Vinogradov, 1972 (Figs. 1–2) Material examined. Mar del Plata, Argentina, station L42 of the Talud II campaign, 37°59.11’S, 54°41.136’W, Slope II, 877 m, (25.V.2013), R/V Puerto Deseado , 1 male (juvenile) cl = 13.61 mm, cw = 12.63 mm, MACN-In 39716. Diagnosis. Carapace subpentagonal or pyriform, slightly longer than wider, covered with long conical spines (Fig. 1). Juveniles have mushroom shape tubercles, with spiniform setae surrounding at the apex. Gastric region with a prominent spine. Branchial regions with acute spines. Lateral and posterior surface with small spines. Rostrum acute trispinose, overreaching the ocular peduncle; paired dorsal spines divergent, directed obliquely upwards, slightly shorter than the central, with a small spine between them (Fig. 2 A). Ocular peduncle with a longest dorsal spine overreaching the cornea; with scattered smaller spines along its length; some spines with several apical setae (Fig. 2 A, B). Scaphocerite slender, armed with a long central acute spine, two lateral smaller spines and one short inner spine (Fig. 2 B). Chelipeds and walking legs densely covered with long and acute spines; dorsal margin with prominent spines; ventral margin armed with blunt spines, in juveniles specimens have blunt tubercles with a tuft of long and rigid setae (Fig. 2 C, D, E). Distribution. Southeast Atlantic, Scotia Sea, South Georgia Island (Birstein & Vinogradov 1972), and between the Burwood Bank and the Malvinas Islands (Macpherson 1988a), and now from Mar del Plata. Depth range: 132 and 877 m. Remarks. The specimen examined agrees with the description by Birstein & Vinogradov (1972) except for the armature of the scaphocerite, which has two pairs of lateral spines, and in the specimen analyzed here, just one spine on the inner side. However, Macpherson (1988b) noted that in the holotype, the inner side of the scaphocerite has three spines; this character may be variable in juvenile and adult specimens. The variations of this new specimen ...